Environmental Education Implementation Analysis by Social Studies Teacher at Junior High School Sukoharjo Regency, Indonesia - Wijayanti, Ary; Rohsulina, Pranichayudha; Ali, M.; Kurniaaji, Bayu (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2024)
Environmental problems pose serious challenges, necessitating urgent action to prevent further damage. Implementing environmental education in junior high schools can engage students in maintaining and preventing environmental harm both within schools and communities. This study aims to evaluate how social studies teachers in Junior High Schools in Sukoharjo Regency implement environmental education and identify their obstacles. Employing a qualitative approach, the research describes data obtained through triangulation techniques, with analysis based on the Miles and Huberman model. Findings reveal that, as of 2022, 36 junior high schools in Sukoharjo Regency have been awarded the Adiwiyata program, categorized into four levels: 33 district-level, 21 provincial-level, four national-level, and four independent-level schools. Positive environmental impacts include maintained cleanliness, reduced pollution, and minimized environmental damage. However, challenges persist, such as limited funding, insufficient quality of human resources, and constrained space. These obstacles hinder the effective implementation of environmental education, underscoring the need for targeted support and resources to enhance program effectiveness.